Analisis Pengelolaan Zakat Di Masa Pandemi Covid-19 - Nuzulia Nuzulia (Jurnal Ilmiah Ekonomi Islam, 2021)
Zakat is an obligation imposed on property owned by every Muslim, from one point of view zakat is worship and from another point of view, it is a social obligation. This study uses a descriptive qualitative approach which is an effort to understand the various concepts found in the research process, using content analysis techniques (content analysis) and library research (library research). This study discusses the utilization of zakat during the COVID-19 pandemic, while also explaining the management of zakat by Baznas before the pandemic. The results of the study show that zakat as an Islamic financial instrument is a potential source for alleviating poverty, especially now that Indonesia is faced with a pandemic condition that causes many negative impacts. Zakat is here to assist the government in restoring the Indonesian economy by providing a different management and distribution system from the previous year, such as distributing zakat funds to be used to buy PPE, establishing isolation rooms, spraying disinfectants, and providing education to the public. In addition, assisting to restore economic conditions caused by the COVID-19 virus such as assistance for family food, cash for work, zakat fitrah, BTM, as well as assistance for laid-off employees or workers.